Regulation of LL-37 in Bone and Periodontium Regeneration - Zahra Chinipardaz; Jessica M. Zhong; Shuying Yang (Life, 2022)
The goal of regenerative therapy is to restore the structure and function of the lost tissues in the fields of medicine and dentistry. However, there are some challenges in regeneration therapy such as the delivery of oxygen and nutrition, and the risk of infection in conditions such as periodontitis, osteomyelitis, etc. Leucine leucine-37 (LL-37) is a 37-residue, amphipathic, and helical peptide found only in humans and is expressed throughout the body. It has been shown to induce neovascularization and vascular endothelial growth factor (VEGF) expression. LL-37 also stimulates the migration and differentiation of mesenchymal stem cells (MSCs). Recent studies have shown that LL-37 plays an important role in the innate defense system through the elimination of pathogenic microbes and the modulation of the host immune response. LL-37 also manifests other functions such as promoting wound healing, angiogenesis, cell differentiation, and modulating apoptosis. This review summarizes the current studies on the structure, expression, and function of LL-37 and highlights the contributions of LL-37 to oral cavity, periodontium, and bone regeneration.